Change in Renal Function and Its Impact on Survival in Chronic Kidney Disease Patients Bridged to Heart Transplantation With a Left Ventricular Assist Device. Issue 11 (22nd March 2021) - Okoh, Alexis K.; Kassotis, John; Shah, Aakash M.; Siddiqui, Emaad; Dhaduk, Nehal; Hirji, Sameer; Gold, Justin; Mehta, Harsh; Ruberwa, Joseph; Soliman, Fady; Tayal, Rajiv; Russo, Mark J; et al.
Abstract : The study investigates the incidence of change in renal function and its impact on survival in renal dysfunction patients who were bridged to heart transplantation with a left ventricular assist device (BTT-LVAD). BTT-LVAD patients with greater than or equal to moderately reduced renal function (estimated glomerular filtration rate [eGFR] ≤ 60 ml/min/1.73 m 2 ) at the time of listing between 2008 and 2018 were identified from a prospectively maintained database of the United Network for Organ Sharing. Patients with a baseline eGFR less than or equal to 15 ml/min/1.73 m 2 or on dialysis were excluded. Patients were divided into three groups based on percent change ([Pretransplant eGFR – listing eGFR/listing glomerular filtration rate (GFR)] × 100) in eGFR: Improvement greater than or equal to 10%, no change, decline greater than or equal to 10%, and their operative outcomes were compared. Posttransplant survival was estimated and compared among the three groups with the Kaplan-Meier survival curves and the log-rank test. Cox proportional hazards modeling was used to identify predictors of posttransplant survival. Out of 14, 395 LVAD patients, 1, 622 (11%) met the inclusion criteria. At the time of transplant, 900 (55%) had reported an improvement in eGFR greater than or equal to 10%, 436 (27%) had no change, and 286 (18%) experienced a decline greater than or equal to 10%. Postoperatively, the incidence of dialysis was higher in the decline than in the unchanged or improved groups (22% vs. 12% vs. 12%; p = 0.002). After a median follow-up of 5 years, there was no difference in posttransplant survival among the stratified groups (improved eGFR: 24.8%, unchanged eGFR: 23.2%, declined eGFR: 20.3%; p = 0.680). On Cox proportional hazard modeling, independent predictors of worse survival were: [hazard ratio: 95% CI; p ] history of diabetes (1.43 [1.13–1.81]; p = 0.002) or tobacco use (1.40 [1.11–1.79]; p = 0.005) and ischemic time greater than 4 hours (1.36 [1.03–1.76]; p = 0.027). More than half of the patients with compromised renal function who undergo BTT-LVAD demonstrate an improvement in renal function at the time of transplant. A 10% change in GFR while listed was not associated with worse posttransplant survival.